PELATIHAN ADVANDCED MICROSOFT EXCEL DALAM MENINGKATKAN KEMAMPUAN SISWA SMK MUHAMMADIYAH 04 - Nasution, Fitri Pranita; Fetty Ade Putri; Rahmad Doni; Mhd Syahrul Ramadhan Girsang (Publikasi Pengabdian Masyarakat, 2023)
Studying ICT (Computer Information Technology) for school students at all levels in this very fast technological development is mandatory. Understanding the use of technology can help many audiences in various fields to solve everyday problems. One of them is the ability to use Advanced Microsoft Excel, where in the world of work the use of high-level Excel formulas is very often used. However, the problem that is often encountered is the lack of support from both the curriculum and schools in learning these formulas. The aim of this service is to provide vocational school students majoring in accounting with an understanding of the importance of knowing Advanced Microsoft Excel and providing hard skills for facing the world of work in the future. The result of this service is increased knowledge, understanding and motivation of vocational school students regarding Advanced Microsoft Excel.